DISFUNGSI TUBA EUSTACHIUS - Tiara Melati (Fakultas Kedokteran Universitas Trisakti, 2024)
Eustachian Tube Dysfunction occurred due to pressure dysregulation of the middle ear leading to negative pressure within the tympanic cavity. This syndrome may be due to intrinsic factor such as anatomical anomaly (cleft palate) and extrinsic factors such as upper respiratory tract infection, laryngpharyngeal reflux, adenoid hypertrophy or other nasopharyngeal mass, mucociliary clearance disorder, and others. The symptoms of this syndrome included obstructed ear or sensation of water filling ear (aural fullness), conductive hearing loss, ringing in the ear, or autophony. This syndrome occurrence frequently seen in allergic rhinitis and chronic rhinosinusitis groups. This article described the basic sciences, diagnosis as well as the latest preventive measures in managing Eustachian Tube Dysfunction. This article aims to increase the medical community awareness about the condition of Eustachian Tube Dysfunction which often unnoticed, to decrease incidence and cost of disease in Indonesia. Examination should consider tools availability and accessible in the primary, secondary and tertiary settings necessary to make diagnosis. The use of statistically validated and reliable questionnaires would improve anamnesis, such as Eustachius Tube Dysfunction Quessionaire-7, Total Nasal Symptoms Score, Nasal Obstruction Symptoms Evaluation, Reflux Symptoms Index. Basic examination of the ear and hearing using otoscopy and tunning fork like Rinne and Weber tests were also useful in the primare care setting. The combination of subjective and objective measurements will boost a better prognosis.